Mutation Spectrum in RAB3GAP1, RAB3GAP2, and RAB18 and Genotype-Phenotype Correlations in Warburg Micro Syndrome and Martsolf Syndrome - Handley, Mark T.; Morris-Rosendahl, Deborah J.; Brown, Stephen; Macdonald, Fiona; Hardy, Carol; Bem, Danai; Carpanini, Sarah M.; Borck, Guntram; Martorell, Loreto; Izzi, Claudia; Faravelli, Francesca; Accorsi, Patrizia; et al. (Human mutation, 2013)
ABSTRACT Warburg Micro syndrome and Martsolf syndrome (MS) are heterogeneous autosomal‐recessive developmental disorders characterized by brain, eye, and endocrine abnormalities. Causative biallelic germline mutations have been identified in RAB3GAP1, RAB3GAP2, or RAB18, each of which encode proteins involved in membrane trafficking. This report provides an up to date overview of all known disease variants identified in 29 previously published families and 52 new families. One‐hundred and forty‐four Micro and nine Martsolf families were investigated, identifying mutations in RAB3GAP1 in 41% of cases, mutations in RAB3GAP2 in 7% of cases, and mutations in RAB18 in 5% of cases. These are listed in Leiden Open source Variation Databases, which was created by us for all three genes. Genotype–phenotype correlations for these genes have now established that the clinical phenotypes in Micro syndrome and MS represent a phenotypic continuum related to the nature and severity of the mutations present in the disease genes, with more deleterious mutations causing Micro syndrome and milder mutations causing MS. RAB18 has not yet been linked to the RAB3 pathways, but mutations in all three genes cause an indistinguishable phenotype, making it likely that there is some overlap. There is considerable genetic heterogeneity for these disorders and further gene identification will help delineate these pathways. Warburg Micro syndrome (OMIM 60018) and Martsolf syndrome (OMIM 21270) are related autosomal recessive neurodevelopmental disorders. Micro syndrome is more severe and characterized by ocular (microphthalmos, microcornea, congenital cataracts and optic atrophy) and neurodevelopmental pathology (microcephaly, polymicrogyria, hypogenesis of the corpus callosum, severe learning disability and progressive limb spasticity) and hypothalamic hypogonadism. Causative germline mutations have been identified in RAB3GAP1 (41% of families), RAB3GAP2 (7% of families) and RAB18 (5% of families) and result in a strikingly consistent phenotype.